PENGARUH KOMPETENSI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA LEMBAGA KURSUS DAN PELATIHAN JUWITA DI KABUPATEN LEBAK - Alfin Nugraha; Noviarti (Pasca Sarjana Universitas Satya Negara Indonesia, 2023)
This research is related to how the influence of competence, work discipline and work environment on employee performance at the Juwita Course and Training Institute in Lebak Regency. The purpose of this study is to identify and analyze the effect of competence, work discipline and work environment simultaneously on employee performance, to identify and analyze the effect of competence partially on employee performance, to determine and analyze the effect of work discipline partially on employee performance, to determine and analyze the effect of the work environment partially on employee performance. Respondents in this study were 100 respondents from Juwita Course and Training Institute students. Methods of data collection using questionnaires. In this research design using Quantitative Causal research, which aims to determine the effect of one or more independent variables on the dependent variable. Data processing is carried out using the Multiple Linear Regression Analysis Model with the help of the SPSS program. The results of this study indicate that the competency variable has a positive and significant influence on employee performance by (0,009), the work discipline variable has a positive and significant effect on employee performance by (0,018), the work environment variable has a positive and significant effect on employee performance by (0,010).